The library of lost and found [large type] - Patrick, Phaedra (Thorndike Press, a part of Gale, a Cengage Company, 2019)
Librarian Martha Storm has always found it easier to connect with books than people--though not for lack of trying. She keeps careful lists of how to help others in her superhero-themed notebook. And yet, sometimes it feels like she's invisible. All of that changes when a book of fairy tales arrives on her doorstep. Inside, Martha finds a dedication written to her by her best friend--her grandmother Zelda--who died under mysterious circumstances years earlier. When Martha discovers a clue within the book that her grandmother may still be alive, she becomes determined to discover the truth. As she delves deeper into Zelda's past, she unwittingly reveals a family secret that will change her life forever.